2021
DOI: 10.3390/molecules26133790
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesized Silver Nanoparticles Immobilized on Activated Carbon Nanoparticles: Antibacterial Activity Enhancement Study and Its Application on Textiles Fabrics

Abstract: This research aimed to enhance the antibacterial activity of silver nanoparticles (AgNPs) synthesized from silver nitrate (AgNO3) using aloe vera extract. It was performed by means of incorporating AgNPs on an activated carbon nanoparticle (ACNPs) under ultrasonic agitation (40 kHz, 2 × 50 watt) for 30 min in an aqueous colloidal medium. The successful AgNPs synthesis was clarified with both Ultraviolet-Visible (UV-Vis) and Fourier Transform Infrared (FTIR) spectrophotometers. The successful AgNPs–ACNPs incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…[14]. It contains different phytochemicals including monoterpene, Sesquiterpene, alcohol, aldehyde, ketones, Esters, phenolic acids, and flavonoids, which act as both reducing agent (converting silver ions to silver atoms) and capping or limiting agent (to limit the silver atom aggregation) [15]. Furthermore, as the AgNPs can also be incorporated into textiles using the insitu method, another equation was derived for the in-situ method.…”
Section: Introductionmentioning
confidence: 99%
“…[14]. It contains different phytochemicals including monoterpene, Sesquiterpene, alcohol, aldehyde, ketones, Esters, phenolic acids, and flavonoids, which act as both reducing agent (converting silver ions to silver atoms) and capping or limiting agent (to limit the silver atom aggregation) [15]. Furthermore, as the AgNPs can also be incorporated into textiles using the insitu method, another equation was derived for the in-situ method.…”
Section: Introductionmentioning
confidence: 99%
“…Other than antimicrobial activity, nanoparticles can impart unique properties to textiles including increased conductivity (Gasana et al 2006 ; Root et al 2018a ), self-cleaning (Allahyarzadeh et al 2013a ), electromagnetic interference shielding (Lu et al 2010 ) and ultraviolet shielding (Shateri-Khalilabad et al 2017 ). A recent push for the development of smart textiles has seen many of these unique properties combined into one material, with many traditional and green synthesis techniques being employed to achieve these multi-application materials (Dhanawansha et al 2020 ; Zhu et al 2020 a, b; Darabi et al 2020 ; Ibrahim et al 2021 ; Wibawa et al 2021 ; Baldwin et al 2021 ; Salama et al 2021 ; Assylbekova et al 2022 ; Galante et al 2022 ). For example, work by Guo et al ( 2021 ) resulted in the development of a textile that maintained its innate flexibility/permeability, while also exhibiting novel properties including rapid thermal response, long-time steady heating performance, and antifouling properties while also being conductive and wate-resistant (Guo et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parameters, such as pore size distribution, surface area, pH, and elemental analysis are used to characterize active carbon products [33,34]. Recent studies have demonstrated that activated carbonsupported metal nanoparticles, prepared from plant (Cassia roxburghii, Aloe vera and Cinnamomum verum) extracts, can yield nanocomposites with superior antibacterial efficiency [35][36][37]. The literature also provides evidence of the use of nanoparticles to develop composites with antimicrobial efficacy [38].…”
Section: Introductionmentioning
confidence: 99%